High-grade ductal carcinoma in-situ detected by microcalcification within borderline phyllodes tumor: Report of a case and literature review - Wing Nam Yuen; Joshua J.X. Li; Man Yi Chan; Gary M. Tse (Elsevier, 2023)
Introduction: Phyllodes tumor is a rare biphasic neoplasm of the breast that mainly affects middle-aged women. Ductal carcinoma in-situ and microcalcifications occurring within phyllodes tumors are rare. Calcifications detected radiologically in this context have been reported but poorly characterized in previous studies. Case presentation: We have encountered a case of a 42-year-old woman with high-grade ductal carcinoma in-situ within a borderline phyllodes tumor. Radiologically, clumps of coarse microcalcifications were detected within the lesion. Local excision followed by total mastectomy with axillary dissection was performed. No tumor recurrence has been detected for eight years. Conclusion: The presence of microcalcification is reported in less than a third (29%) of phyllodes tumors with a carcinoma component. Both benign-looking specks and suspicious coarse punctate clusters of microcalcifications had been described. The presence of microcalcifications within a phyllodes tumor should alert clinicians and pathologists of possible coexisting carcinoma components. Primary surgical excision with adjuvant therapies remains the mainstay of treatment.